Assessing Durability and Stability of Calcium Sulfoaluminate Cement-Stabilized Soils Under Cyclic Wet–Dry Conditions - Ayesha Rauf; Sung-Woo Moon; Alfrendo Satyanaga; Jong Kim (Buildings)
Periodic wet–dry processes are a significant weathering mechanism that can quickly alter a soil’s mechanical characteristics, reducing its resilience and durability. This study investigates the physical and microstructural characterization of stabilized soils through experimental analysis. While the conventional approach to ground improvement involves the application of ordinary Portland cement (OPC) and lime for treating unstable soil, this research explores calcium sulfoaluminate (CSA) cement as an eco-friendly alternative with comparable efficacy and fewer adverse environmental effects. The primary objective is to evaluate the impact of cyclic wet–dry (W–D) events on the durability and stability of CSA cement-treated sand using comprehensive laboratory testing. Various samples were prepared with cement contents of 3%, 5%, 7%, and 10%, corresponding to the optimum moisture content. Stabilized soil specimens underwent testing for unconfined compressive strength (UCS) and ultrasonic pulse velocity (UPV) after curing for 3, 7, 14, and 28 days. Subsequently, these specimens were exposed to zero, one, three, five, and seven W–D cycles. The outcomes show a decrease in the strength and durability index of the soil with a rising number of W–D cycles. However, the decline in the strength and durability of CSA-treated soil samples is significantly mitigated as the CSA content increases from 3% to 10%. The findings indicate that after seven W–D cycles, the UCS value of 10% cemented samples dropped by 14% after 28 days of curing, whereas 3% specimens experienced a 28% loss in strength. Similarly, UCS values for 5% and 7% cement content reduced from 666 kPa to 509 kPa and from 1587 kPa to 1331 kPa, respectively, indicating improved resilience with higher CSA content. The durability index was less affected during the first three cycles, but showed a more pronounced decline after five and seven cycles. For 3% cemented soil, the durability index dropped from 0.95 to 0.71, whereas for 10% cemented soil, it decreased from 0.97 to 0.82 after seven W–D cycles. The scanning electron microscope (SEM) also determines the cement–soil interaction before and after W–D, and it was noted that the pores and cracks increased after each cycle. Based on the findings, it is established that subgrade materials treated with CSA cement demonstrate durability, environmental sustainability, and suitability for integration into road construction projects.